LAJU INFLASI DAMPAKNYA TERHADAP PEREKONOMIAN INDONESIA DAN CARA PENANGGULANGANNYA - Hadi, Seno Sudarmono (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2016)
Inflation occurred in Indonesia can impact positively or negatively on the economy globally, depending on the height of the low inflation rate is concerned.If inflation mild dampat is impacting positively on the economy of a society that is able to raise the level of national income and enhance people's interest for saving becomes even higher.The recipient of a fixed regular income each month as civil servants, private employees and workers are increasingly eager to do his work activities to improve the quality of life.While the stable inflation can improve financial planning dimasyarakat better, purchasing power against goods and services become more affordable so that the necessities of life are met, investing more smoothly because the motive is not a speculative investment and bank credit more smoothly, and if this situation happened in quite a long period of time will cause the real income of the society become stable, standard of living and welfare of the community miningkat. For the corporate world in areas such as trade in financial reports produced positive financial balance while the value of the country is relatively stable, whereas the heavy inflation or uncontrolled (Hyperinflasi) resulted in a decline in the economy of the community or the slack economic growth Countries. Based on the above research titles then the researcher explores how tackling the possibility of inflation in terms of deregulation or the policies conducted at Bank Indonesia especially the Government as monetary authorities in Indonesia so as to prevent a decline in economic growth as well as the slack economy of Indonesia in particular